DEVELOPMENT OF METHODOLOGICAL FOUNDATIONS FOR THE DESIGN OF LOGGING INFRASTRUCTURE TAKING INTO ACCOUNT THE DYNAMICALLY CHANGING ENVIRONMENT - Mokhirev, Aleksandr; Rukomojnikov, Konstantin; Gerasimova, Marina; Medvedev, Sergey (Journal of Applied Engineering Science, 2020)
Development of forest resources is currently associated with significant difficulties, primarily due to unsatisfactory infrastructure in greater part of the forest area. It is necessary to create an effective, mathematically based forest infrastructure so that the forest industry will be developing actively. This will create the prerequisites for effective continuous and sustainable use of the forest. At the same time, the transport and economic availability of wood resources will increase significantly. There are many options for organizing the logging process by forestry enterprises. In most cases, they are selected by management based on personal experience. This study is a continuation of the work of the author's team on the complex problem of algorithmization and optimization of logging operations, taking into account the analysis of various moving and processing operations of wood resources. In previous publications, the authors presented a graphic-analytical model for solving the task. This article presents a description of the algorithm developed on the basis of the presented mathematical and graphic-analytical models for finding an effective technological chain of transport, loading and unloading and processing operations of the logging process in dynamic natural production conditions. The developed algorithm can be considered as a methodological basis for logging infrastructure design, taking into account the dynamically changing environment.
Keywords: algorithm, graph, forest infrastructure, logging process, graphic-analytical model